Commitment organizational as predictor of emotional intelligence - Salvador-Ferrer, Carmen María (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
The intention of this study consists of studying meticulously the relation between the commitment of the workers and the emotional intelligence. For it, there is exposed an investigation that includes changeable paths. There was obtained information of 165 workers of a company of the car sector. Besides, we propose a model of the emotional intelligence, to test it applies to himself an analysis of structural equations In this respect, the information comes to reflect the great influence that has the normative commitment on the emotional intelligence.